Colonization and Community: The Vancouver Island Coalfield and the Making of the British Columbian Working Class - Belshaw, John Douglas (McGill-Queen's University Press, 2002)
An examination of the social, political, and demographic history of British miners and their households on Vancouver Island in the nineteenth century. In the nineteenth century coal-miners imported from Europe, Asia, and eastern North America burrowed beneath the Vancouver Island towns of Nanaimo, Wellington, and Cumberland. No group was as numerous and influential in this enterprise as the hundreds of British immigrants who traveled half-way around the world to take up back-breaking work in the most remote colony in the Empire. What drew the British miners and their families to the north Pacific? Why did they set aside six months to journey to a colony about which they knew little? Once they reached Vancouver Island, what did they make of it and what did they make it into? And how did they re-make themselves in the process? In Colonization and Community John Belshaw takes a new look at British Columbia's first working class, the men, women, and children beneath and beyond the pit-head. Beginning with an exploration of emigrant expectations and ambitions, he investigates working conditions, household wages, racism, industrial organization, gender, schooling, leisure, community building, and the fluid identity of the British mining colony, the archetypal west coast proletariat. By connecting the story of Vancouver Island to the larger story of Victorian industrialization, he delineates what was distinctive and what was common about the lot of the settler society. Belshaw breaks new ground, challenging the easy assumptions of transferred British political traditions, analyzing the colonial at the household level, and revealing the emergent communities of Vancouver Island as the cradle of British Columbian working-class culture. –Publisher's description